Method for dissolving TaAl alloy

By heating the TaAl alloy under the synergistic action of hydrofluoric acid and hydrochloric acid, the volume ratio of hydrofluoric acid and hydrochloric acid is controlled, the problem of difficulty in dissolution of TaAl alloy is solved, and the rapid and efficient dissolution and component detection of TaAl alloy are achieved.

CN119845675APending Publication Date: 2025-04-18KONFOONG MATERIALS INTERNATIONAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510036765.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art fails to effectively dissolve TaAl alloys, making it difficult to detect its components.

Method used

Under the synergistic action of hydrofluoric acid and hydrochloric acid, the TaAl alloy is heated to control the volume ratio of hydrofluoric acid and hydrochloric acid to be fully dissolved to obtain a dissolving solution suitable for ICP-OES detection.

Benefits of technology

This method can quickly and efficiently dissolve TaAl alloy, reduce heating temperature and time, improve detection efficiency, and obtain a dissolving solution suitable for ICP-OES detection.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for dissolving a TaAl alloy. The method comprises the steps that TaAl alloy, hydrofluoric acid and hydrochloric acid are mixed and then heated, and a dissolving solution is obtained; wherein the volume ratio of the hydrofluoric acid to the hydrochloric acid is (4-6): 1. According to the method for dissolving the TaAl alloy, under the synergistic effect of hydrofluoric acid and hydrochloric acid, the TaAl alloy can be completely dissolved, and the dissolving solution suitable for ICP-OES detection is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of analytical chemistry and relates to a method for dissolving TaAl alloy. Background Art

[0002] TaAl alloy is an alloy material that can be used in the field of high-temperature alloy ingot manufacturing and semiconductor fields. For example, CN116926377A discloses a large-scale high-temperature titanium alloy ingot and a preparation method thereof, including: uniformly mixing titanium sponge, aluminum beans, niobium alloy, HZr, MoAl, TaAl, WAl, SnTi, TiSi, high-purity flake graphite, and TiO2, and then pressing an electrode block to obtain an electrode block; welding the electrode block in a plasma welding box to obtain a consumable electrode; and performing three vacuum consumable melting on the consumable electrode to obtain a titanium alloy ingot. When selecting the intermediate alloy, the content of impurity elements such as Fe and Ni is strictly controlled to improve the purity of the high-temperature titanium alloy ingot. The problem of easy cracking of high-temperature titanium alloy welding is solved, the safety and stability of the smelting process are guaranteed, and the segregation problem of Mo, Nb, Ta, and W elements is solved, thereby obtaining a large-scale, highly uniform high-temperature titanium alloy ingot.

[0003] CN103258823A relates to a semiconductor structure and a method for forming the same. A tantalum alloy layer is used as a work function metal for a field effect transistor. The tantalum alloy layer may be selected from TaC, TaAl, and TaAlC. When used in combination with a metal nitride layer, the tantalum alloy layer and the metal nitride layer provide two work function values ​​that differ by 300 mV to 500 mV, thereby realizing a plurality of field effect transistors with different threshold voltages. The tantalum alloy layer may contact a first gate dielectric in a first gate, and the metal nitride layer may contact a second gate dielectric having the same composition and thickness as the first gate dielectric and being located in the second gate.

[0004] The specific content of Ta and Al in TaAl alloy has an important influence on its performance, so it needs to be tested for composition. At present, inductively coupled plasma optical emission spectrometer (ICP-OES) is generally used to detect the composition of metal materials. ICP-OES has the advantages of less interference, stable signal, simple operation, etc., and can detect most metal elements and some non-metallic elements. When using ICP-OES for detection, the metal material to be tested needs to be dissolved and the obtained solution needs to be tested on the machine, but there is currently no method for dissolving TaAl alloy.

[0005] Therefore, there is an urgent need to provide a method for dissolving TaAl alloy. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a method for dissolving TaAl alloy. In the method for dissolving TaAl alloy provided by the present invention, under the synergistic effect of hydrofluoric acid and hydrochloric acid, the TaAl alloy can be completely dissolved to obtain a dissolving solution suitable for ICP-OES detection.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for dissolving TaAl alloy, the method comprising:

[0009] TaAl alloy, hydrofluoric acid and hydrochloric acid are mixed and then heated to obtain a solution; wherein the volume ratio of the hydrofluoric acid to the hydrochloric acid is (4-6):1, for example, it can be 4:1, 5:1 or 6:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0010] The invention provides a method for dissolving a TaAl alloy. Under the synergistic effect of hydrofluoric acid and hydrochloric acid, the TaAl alloy can be completely and fully dissolved to obtain a dissolving solution suitable for ICP-OES detection. When the volume ratio of hydrofluoric acid to hydrochloric acid is controlled to be (4-6):1, hydrofluoric acid and hydrochloric acid have a stronger ability to dissolve the TaAl alloy. While the TaAl alloy is completely and fully dissolved, the temperature required for heating can be reduced, and the time required for heating can be reduced, so that the TaAl alloy dissolving solution can be obtained quickly and efficiently.

[0011] Preferably, based on the total mass of the TaAl alloy, the mass fraction of the Al element in the TaAl alloy is 15-20%, for example, 15%, 17% or 20%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] Preferably, the mass concentration of the hydrofluoric acid is 38-42%, for example, 38%, 40% or 42%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0013] Preferably, the mass concentration of the hydrochloric acid is 36.5-38.5%, for example, 36.5%, 37% or 38%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the ratio of the mass of the TaAl alloy to the total volume of the hydrofluoric acid and the hydrochloric acid is 1g:(20-40)mL, for example, it can be 1g:20mL, 1g:22mL, 1g:24mL, 1g:25mL, 1g:28mL, 1g:30mL, 1g:32mL, 1g:35mL, 1g:38mL or 1g:40mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0015] Preferably, the specific steps of mixing include: firstly placing the TaAl alloy in a container, and then adding hydrofluoric acid and hydrochloric acid into the container.

[0016] Preferably, the heating temperature is 80-85°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In the present invention, under the synergistic effect of hydrofluoric acid and hydrochloric acid in a volume ratio of (4-6):1, the temperature required for heating is relatively low, and the TaAl alloy can be completely dissolved within the above preferred range.

[0018] Preferably, the heating time is 25-45 min, for example, it can be 25 min, 28 min, 30 min, 32 min, 35 min, 38 min, 40 min, 42 min or 45 min, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In the present invention, under the synergistic effect of hydrofluoric acid and hydrochloric acid in a volume ratio of (4-6):1, the time required for heating is short, and the TaAl alloy can be completely dissolved within the above preferred range with high efficiency.

[0020] Preferably, after the heating, a volume fixing step is further performed.

[0021] As a preferred technical solution of the present invention, the method specifically comprises the following steps:

[0022] (1) placing a TaAl alloy in a container, and then adding hydrofluoric acid and hydrochloric acid into the container; wherein, based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 15-20%; the mass concentration of the hydrofluoric acid is 38-42%; the mass concentration of the hydrochloric acid is 36.5-38.5%; the volume ratio of the hydrofluoric acid to the hydrochloric acid is (4-6):1; and the ratio of the mass of the TaAl alloy to the total volume of the hydrofluoric acid and the hydrochloric acid is 1 g:(20-40) mL.

[0023] (2) placing the container in a graphite heater, heating at 80-85° C. for 25-45 min, and then fixing the volume to obtain a dissolved solution.

[0024] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0025] The present invention is an improved invention of CN114778240A.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The invention provides a method for dissolving a TaAl alloy. Under the synergistic effect of hydrofluoric acid and hydrochloric acid, the TaAl alloy can be completely and fully dissolved to obtain a dissolving solution suitable for ICP-OES detection. When the volume ratio of hydrofluoric acid to hydrochloric acid is controlled to be (4-6):1, hydrofluoric acid and hydrochloric acid have a stronger ability to dissolve the TaAl alloy. While the TaAl alloy is completely and fully dissolved, the temperature required for heating can be reduced, and the time required for heating can be reduced, so that the TaAl alloy dissolving solution can be obtained quickly and efficiently. DETAILED DESCRIPTION

[0028] The technical scheme of the present invention is further described below by specific implementation methods. For ease of understanding the present invention, the present invention lists the following embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0029] Example 1

[0030] This embodiment provides a method for dissolving TaAl alloy, comprising the following steps:

[0031] (1) Weigh 0.1 g of TaAl alloy and put it into a polytetrafluoroethylene tube, then add 2 mL of hydrofluoric acid and 0.5 mL of hydrochloric acid to mix; wherein, based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 18%; the mass concentration of the hydrofluoric acid is 40%; and the mass concentration of the hydrochloric acid is 37%.

[0032] (2) The polytetrafluoroethylene tube is placed in a graphite heater and heated at 80° C. for 30 min to obtain a clear and transparent solution, which is then fixed to a fixed volume to obtain a dissolved solution.

[0033] Example 2

[0034] This embodiment provides a method for dissolving TaAl alloy, comprising the following steps:

[0035] (1) Weigh 0.1 g of TaAl alloy and put it into a polytetrafluoroethylene tube, then add 2 mL of hydrofluoric acid and 0.4 mL of hydrochloric acid to mix; wherein, based on the total mass of the TaAl alloy, the mass fraction of the Al element in the TaAl alloy is 15%; the mass concentration of the hydrofluoric acid is 42%; and the mass concentration of the hydrochloric acid is 36.5%.

[0036] (2) The polytetrafluoroethylene tube is placed in a graphite heater and heated at 85° C. for 25 min to obtain a clear and transparent solution, which is then fixed to a fixed volume to obtain a dissolved solution.

[0037] Example 3

[0038] This embodiment provides a method for dissolving TaAl alloy, comprising the following steps:

[0039] (1) Weigh 0.1 g of TaAl alloy and put it into a polytetrafluoroethylene tube, then add 3 mL of hydrofluoric acid and 0.5 mL of hydrochloric acid to mix; wherein, based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 20%; the mass concentration of the hydrofluoric acid is 38%; and the mass concentration of the hydrochloric acid is 38.5%.

[0040] (2) The polytetrafluoroethylene tube is placed in a graphite heater and heated at 80° C. for 30 min to obtain a clear and transparent solution, which is then fixed to a fixed volume to obtain a dissolved solution.

[0041] It can be seen from Examples 1-3 that by adopting the method for dissolving TaAl alloy provided by the present invention, under the synergistic action of hydrofluoric acid and hydrochloric acid, the TaAl alloy can be quickly and efficiently dissolved completely and fully, and the finally obtained dissolution solution meets the standard for ICP-OES on-machine detection, and the contents of Ta and Al elements can be detected.

[0042] Example 4

[0043] This embodiment provides a method for dissolving TaAl alloy, comprising the following steps:

[0044] (1) Weigh 0.1 g of TaAl alloy and put it into a polytetrafluoroethylene tube, then add 2 mL of hydrofluoric acid and 0.5 mL of hydrochloric acid to mix; wherein, based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 18%; the mass concentration of the hydrofluoric acid is 40%; and the mass concentration of the hydrochloric acid is 37%.

[0045] (2) The polytetrafluoroethylene tube is placed in a graphite heater, heated at 75° C. for 30 min, and then fixed to a constant volume to obtain a solution.

[0046] Example 5

[0047] This embodiment provides a method for dissolving TaAl alloy, comprising the following steps:

[0048] (1) Weigh 0.1 g of TaAl alloy and put it into a polytetrafluoroethylene tube, then add 2 mL of hydrofluoric acid and 0.5 mL of hydrochloric acid to mix; wherein, based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 18%; the mass concentration of the hydrofluoric acid is 40%; and the mass concentration of the hydrochloric acid is 37%.

[0049] (2) The polytetrafluoroethylene tube is placed in a graphite heater, heated at 90° C. for 30 min, and then fixed to a constant volume to obtain a solution.

[0050] It can be seen from Example 1 and Example 4-5 that when the heating temperature is controlled within a limited range, the TaAl alloy can be completely and fully dissolved, and energy consumption can be reduced and resources can be saved. When the heating temperature is too low, the TaAl alloy cannot be completely and fully dissolved, and the obtained solution cannot be used for ICP-OES detection. When the heating temperature is too high, it will cause the elements to volatilize and the test results will be low.

[0051] Comparative Example 1

[0052] This comparative example provides a method for dissolving TaAl alloy, comprising the following steps:

[0053] (1) Weigh 0.1 g of TaAl alloy and put it into a polytetrafluoroethylene tube, then add 2 mL of hydrofluoric acid and 0.5 mL of nitric acid to mix; wherein, based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 18%; the mass concentration of the hydrofluoric acid is 40%; and the mass concentration of the nitric acid is 66%.

[0054] (2) The polytetrafluoroethylene tube is placed in a graphite heater, heated at 80° C. for 30 min, and then fixed to a constant volume to obtain a solution.

[0055] It can be seen from Example 1 and Comparative Example 1 that if nitric acid and hydrofluoric acid are used to dissolve the TaAl alloy, the nitric acid will react with Al to form an oxide film, which is not conducive to the dissolution of the TaAl alloy sample.

[0056] Comparative Example 2

[0057] This comparative example provides a method for dissolving TaAl alloy, comprising the following steps:

[0058] (1) Weigh 0.1 g of TaAl alloy and put it into a polytetrafluoroethylene tube, then add 1.875 mL of hydrofluoric acid and 0.625 mL of hydrochloric acid to mix; wherein, based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 18%; the mass concentration of the hydrofluoric acid is 40%; and the mass concentration of the hydrochloric acid is 37%.

[0059] (2) The polytetrafluoroethylene tube is placed in a graphite heater, heated at 80° C. for 30 min, and then fixed to a constant volume to obtain a solution.

[0060] Comparative Example 3

[0061] This comparative example provides a method for dissolving TaAl alloy, comprising the following steps:

[0062] (1) Weigh 0.1 g of TaAl alloy and put it into a polytetrafluoroethylene tube, then add 2.1875 mL of hydrofluoric acid and 0.3125 mL of hydrochloric acid to mix; wherein, based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 18%; the mass concentration of the hydrofluoric acid is 40%; and the mass concentration of the hydrochloric acid is 37%.

[0063] (2) The polytetrafluoroethylene tube is placed in a graphite heater, heated at 80° C. for 30 min, and then fixed to a constant volume to obtain a solution.

[0064] It can be seen from Example 1 and Comparative Examples 2-3 that when the volume ratio of hydrofluoric acid to hydrochloric acid is controlled within a limited range, hydrofluoric acid and hydrochloric acid have a stronger ability to dissolve TaAl alloys, and while completely and fully dissolving the TaAl alloy, the temperature required for heating can be reduced, and the time required for heating can be reduced, so that the TaAl alloy solution can be obtained quickly and efficiently. When the volume ratio of hydrofluoric acid to hydrochloric acid is too low, the dissolution rate and the dissolution effect will be affected, the dissolution will be incomplete, and a clarified digestion solution cannot be obtained; when the volume ratio of hydrofluoric acid to hydrochloric acid is too high, the TaAl alloy sample can be dissolved, but the HF concentration is too high, which causes great damage to the equipment.

[0065] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for dissolving TaAl alloy, characterized in that: The method comprises: The TaAl alloy, hydrofluoric acid and hydrochloric acid are mixed and then heated to obtain a solution; Wherein, the volume ratio of the hydrofluoric acid to the hydrochloric acid is (4-6):

1.

2. The method according to claim 1, characterized in that: Based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 15-20%.

3. The method according to claim 1 or 2, characterized in that: The mass concentration of the hydrofluoric acid is 38-42%.

4. The method according to any one of claims 1 to 3, characterized in that: The mass concentration of the hydrochloric acid is 36.5-38.5%.

5. The method according to any one of claims 1 to 4, characterized in that: The ratio of the mass of the TaAl alloy to the total volume of the hydrofluoric acid and the hydrochloric acid is 1 g:(20-40) mL.

6. The method according to any one of claims 1 to 5, characterized in that: The specific steps of the mixing include: firstly placing the TaAl alloy in a container, and then adding hydrofluoric acid and hydrochloric acid into the container.

7. The method according to any one of claims 1 to 6, characterized in that: The heating temperature is 80-85°C.

8. The method according to any one of claims 1 to 7, characterized in that: The heating time is 25-45 minutes.

9. The method according to any one of claims 1 to 8, characterized in that: After the heating, a step of fixing the volume is also performed.

10. The method according to any one of claims 1 to 9, characterized in that: The method specifically comprises the following steps: (1) placing a TaAl alloy in a container, and then adding hydrofluoric acid and hydrochloric acid into the container; wherein, based on the total mass of the TaAl alloy, the mass fraction of Al element in the TaAl alloy is 15-20%; the mass concentration of the hydrofluoric acid is 38-42%; the mass concentration of the hydrochloric acid is 36.5-38.5%; the volume ratio of the hydrofluoric acid to the hydrochloric acid is (4-6):1; the ratio of the mass of the TaAl alloy to the total volume of the hydrofluoric acid and the hydrochloric acid is 1 g:(20-40) mL; (2) placing the container in a graphite heater, heating at 80-85° C. for 25-45 min, and then fixing the volume to obtain a dissolved solution.

Citation Information

Patent Citations

  • Semiconductor structure and formation method thereof

    CN103258823A

  • Large-size high-temperature titanium alloy cast ingot and preparation method thereof

    CN116926377A

  • Fast dissolution method of indissolvable alloy sample

    CN105987835A

  • Mixed acid for dissolving chromium-tantalum-titanium alloy as well as preparation method and application thereof

    CN111879845A